Effects of soil degradation and organic treatments on vegetative growth, yield and grape quality - JAVIER TARDAGUILA (EQA, 2018)
Delimited degraded soil areas caused by an improper land preparation before vine plantation and or management can be observed in conventional and organic European vineyards. Soil malfunctioning including: poor organic matter content, imbalanced nutritional status, altered pH, water deficiency, soil compaction and/or scarce oxygenation. The goal of the present study was to compare the effects of some agronomic strategies to restore optimal soil functionality in degraded areas in organic commercial vineyards located in five countries, and to evaluate the impact of these soil management practices on vegetative growth, yield and grape quality parameters. Grapevines located in non-degraded soils showed higher vegetative growth and yield, and lower total soluble solids in grapes. Generally, there were no significant differences in vegetative growth, yield and grape quality among the soil management strategies in degraded areas.